ORAL CAVITY PHYSIOLOGY AND ITS FUNCTIONS (Modern education and development, 2025)
The oral cavity is the initial site of digestion and plays a critical role in food intake, mastication, and enzymatic breakdown. Additionally, it contributes to speech, taste perception, and immune defense. This article provides an overview of the physiology of the oral cavity and its essential functions.